Critical care needs and anxiety levels among family members of ICU patients - Catu, Mayree Diaz
Patients in the ICU are at high risk of dying and this situation concerns most of the family members of patients in ICU. Considering holistic nursing care, nurses should not only care for an ICU patient alone, but rather care for the family of the patient as well. Family is part of the patients care system and how well a family adapts in times of critical illness, may affect the early recovery of the patient. Several studies reported that family members of patients admitted in ICU experience high levels of stress due to anxiety, depression, trauma and psychological distress. -- Aside from levels of anxiety that the family members of ICU patients experiences; there is also emerging various critical care family needs. There have been various studies done to assess family needs but most were abroad. Also, several institutions lack protocols addressing family needs of patients in the ICU. Nurses also pay little attention in caring for the family members of the patient because their main concern are the critically ill patients. In light of these observations, this study sought to determine the anxiety levels and critical care needs among family members of patients in intensive care units of a tertiary hospital. -- To answer this, a descriptive correlational study was done which included 51 family members of patients confined in ICUs of a tertiary hospital. Participants were asked to answer the STAI (State Trait Anxiety) questionnaire to assess their anxiety level and the CCFNI (Critical Care Family Needs Inventory) to determine their needs. -- The study showed that there is increased level of anxiety among family members of patients confined in ICU’s. The result suggest that most of the caregivers of patients in the intensive care unit perceive that there is needed additional need for nursing care not only for the patients but for their families as well. However, the result of the study showed that no association exists between the level of anxiety and perceived total critical care family needs in the current study (p: 0.0133, p-value: 0.93). This suggests that anxiety does not appear to significantly contribute to the perceived importance of family needs to care for their relatives in the critical care units. On the contrary, in the family needs subscale, there is significant correlation (p: - 0.986; p value : 0.000) between length of patients stay and comfort (p: - 0.986; p value: 0.000), assurance (p: - 0.836; p value: 0.019) and information (p: - 0.945; p value: 0.000). This denotes that the longer the length of hospitalization, the less the perceived family need for comfort, assurance and information. -- The study also showed that there is no difference on the anxiety and critical care family needs among family members of ICU patients when grouped according to age, sex, relationship of the family member to the patient, type of ICU, length of hospitalization & the family member’s previous experience in ICU. However, it can be noted that respondents from unskilled occupations have lower perceptions of anxiety than skilled professionals (t:3.56, df: 20.94, p<0.01). In addition to that, men (96.7327.29) were found to rate the needs higher than women (97.3317.28) did. No significant differences in the rating scores across educational attainment, disease condition of affected relative and unit of confinement were also observed. -- The study showed that there was increased level of anxiety among family members of patients confined in ICU’s, thus it is recommended to have anxiety reducing measures designed for family members of patients in ICU. Moreover, further study is needed to determine association between anxiety and critical care family needs. Although, this study revealed that family needs are largely met, there is still some needs that are not met which may be addressed by making the watchers/relatives’ room more comfortable and culture sensitive.